2016
DOI: 10.1111/ssqu.12242
|View full text |Cite
|
Sign up to set email alerts
|

Residential Racial Diversity: Are Transracial Adoptive Families More Like Multiracial or White Families?*

Abstract: Objective. The purpose of this article is to examine whether and how the residential racial diversity of transracially adopted children (i.e., nonwhite children adopted by white parents) varies from those of biological children in white monoracial families and biological children in mixed-race families. Method. Using the restricted access 2009 American Community Survey, we take advantage of the large number of adoptive families not only to investigate differences among these families, but also to explore wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Another possibility is adopted adolescents may not yet have reached a developmental stage where racial and ethnic differences are salient experiences. Most adopted adolescents live in White communities where pressures may exist to de-emphasize racial and ethnic differences (Krieder & Raleigh, 2011). Some adoptees may not begin exploring the importance of their racial and ethnic differences until they have left their communities of origin (Hubinette & Tigervall, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is adopted adolescents may not yet have reached a developmental stage where racial and ethnic differences are salient experiences. Most adopted adolescents live in White communities where pressures may exist to de-emphasize racial and ethnic differences (Krieder & Raleigh, 2011). Some adoptees may not begin exploring the importance of their racial and ethnic differences until they have left their communities of origin (Hubinette & Tigervall, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Today, 59% of internationally adopted children are from Asian countries (U.S. Department of Health & Human Services, 2013), with more than 105,000 Asian adopted children living in U.S. households with White parents in 2009 (Krieder & Raleigh, 2011). More than 80% of international adoptions are considered transracial with White parents and children who are racial and ethnic minorities in the United States (U.S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has found that transracial adoptees were less likely to feel uneasy about their appearance and have fewer adjustment issues when living in communities that were not predominantly white (Feigelman 2000). Research also indicates that transracial adoptees with white parents tend to live in communities with less racial-ethnic diversity compared with children of interracial couples (Kreider and Raleigh 2011). The choices that adoptive parents make as they socialize children have consequences for adoptee identity, attitudes, and experiences (Freundlich 2000; Grotevant et al 2000; Huh and Reid 2000; McGinnis et al 2009; McHale et al 2006; Samuels 2009).…”
Section: Race Neighborhoods and Schoolsmentioning
confidence: 99%
“…Similar to the concept of culture keeping, racial socialization consists of demonstrating behaviors to navigate race, providing opportunities for interaction, and introducing environments, objects, and ideas (Thorton et al 1990 as cited by Brown 2008:33). Both racial socialization practices and child outcomes are shaped by neighborhood context, illustrating the importance of neighborhood choice and composition in conjunction with racial socialization (Caughy et al 2006; Kreider and Raleigh 2011). The present study builds on this premise to ask how white adoptive parents explain decisions of where to send their transracially adopted children to school, whom to befriend, and neighborhood choice.…”
mentioning
confidence: 99%